Keamanan Manusia dalam Perspektif Studi Keamanan Kritis Terkait Perang Intra-Negara - Rizal Adhitya Hidayat (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2017)
This article tries to propose the human security issue that explained by critical security studies approach as an ontological and epistemological critique to state security as the object referent. The critique comes from the wider development of the Copenhagen School promoted by Buzan, Weaver and de Wilde (1998) through the security sector analysis and securitization concepts. Both of those are responded by the critical security studies approach from Aberystwyth/Wales School and the Toronto School which is proposing the three questions of ontological claims through the true and real security concept. This three ontological claims are: what is real (of security)?, what is knowledge (of security)?, what (security) is to be done?. By the deepening relevance to intra-state conflict, the claim of security concepts find the momentum that the threat of security of intra-state conflict/war can arise in all aspects of human life and then following the true and real security threat to the security of human life as a whole.